Preparation of Well-Defined Poly(styrene-co-acrylonitrile)/ZnO Hybrid Nanoparticles by an Efficient Ligand Exchange Strategy - Wang, Zongyu; Mahoney, Clare; Yan, Jiajun; Lu, Zhao; Ferebee, Rachel; Luo, Danli; Bockstaller, Michael R; Matyjaszewski, Krzysztof (Langmuir, 2016)
Poly(styrene-co-acrylonitrile) (PSAN)-capped ZnO nanoparticles (NPs) were synthesized by a “ligand exchange” method. First, octylamine (OA)-capped ZnO NPs were prepared by reaction of OA and zinc 2-ethylhexanoate (Zn(EH)2). Then PSAN polymer ligands were synthesized by activators regenerated by electron transfer (ARGET) atom transfer radical polymerization (ATRP) and were efficiently exchanged with OA ligands on the ZnO particle surface benefiting from the relatively low boiling point of OA (175 °C). The morphology, content of ZnO, and grafting density of the nanocomposite were well controlled by altering the ratio between OA and polymer ligands as well as the molecular weight of PSAN-NH2 used in the exchange reaction. The resulting ZnO/polymer nanocomposites were stable in THF with narrow size distributions and varying grafting densities from 0.9 to 2.5 nm–2. With excess amount of polymer ligands, individual dispersed ZnO NPs were observed. However, with a limited amount of ligands, NPs clusters were formed, as confirmed by TEM and DLS.